Stability conditions of TS fuzzy systems with switched polynomial Lyapunov functions - Elias, Leandro J.; Faria, Flávio A. [UNESP]; Araujo, Rayza; Oliveira, Vilma A. (Elsevier, 2020)
Exploring properties of membership functions, sufficient conditions based on linear matrix inequalities (LMIs) for a existence of a switched polynomial Lyapunov function are proposed. To obtain the LMIs, the time derivative of membership functions are described as a finite polytopic representation, leading to less conservative conditions than other published results. A numerical example illustrates the efficiency of the stabilizing conditions.
Keywords: Linear matrix inequalities; Polynomial Lyapunov functions; Stability analysis; TS fuzzy system